Examining Parental Involvement in Rural, Urban, and Suburban Schools - Doris L. Prater; Andrea B. Bermudez; Emiel Owens (Journal of Research in Rural Education, 1997)
The benefits of parental involvement in the schools has been extensively documented in the research literature (Bermudez, 1994; Epstein, 1987; Epstein & Dauber, 1991; Henderson, 1989).These include improved student achievement (Epstein, 1987; Klaus & Gray, 1968; Schaefer, 1972; Walberg, 1984) and overall school behavior (Levenstein, 1974; Weikart, 1973). In addition, parent-child relationships and home-school relations are also enhanced when parents become involved in their children's education (Bermudez & Padr6n, 1987, 1988; Henderson, 1989; Herman & Yeh, 1980; Met, 1987; Morgan, 1982)